Evaluation of Jeevamruta as a Bio-resource for Nutrient Management in Aerobic Rice - Kasbe, Sudhanshu S.; Joshi, Mukund; Bhaskar, S.; Gopinath, K. A.; Kumar, M. K. (International Journal of Bio-resource and Stress Management, 2023)
In the wake of optimization in use of on-farm resources in crop cultivation a field experiment was conducted during summer season on a red sandy loam soil under irrigated conditions to evaluate the jeevamruta (organic liquid formulation consisting cattle excretions, jaggery, pulse flour and soil in water) for nutrient management in aerobic rice. The study involved jeevamruta, vermicompost and biofertilizer along with chemical fertilizers, on growth and yield of aerobic rice (Oryza sativa L.), soil properties and economics. Application of 100% recommended dose of fertilizers (RDF) along with jeevamruta (based on crop N requirement) and vermicompost being at par with RDF+vermicompost, RDF+jeevamruta and RDF+jeevamruta+biofertilizers (Azospirillum brasilense) gave significantly higher grain yield (5.27 t ha-1) compared to other treatments. Jeevamruta could perform well in integration with chemical fertilizers (as addition) rather than when tried to substitute 50% or 100% recommended dose of nitrogen through it. Integrated nutrient management (INM) involving application of 100% RDF+jeevamruta (2000 L ha-1) with or without biofertilizers gave higher benefit:cost ratio compared to other treatments. The study advocates that jeevamruta is an efficient bio-resource and could be a component of INM for aerobic rice.